FACTORS RELATED TO THE SUCCESS OF THE TREATMENT PROGRAM OF MULTIDRUG-RESISTANT TUBERCULOSIS IN POLYCLINIC OF MDR-TB OF THE GENERAL HOSPITAL OF UNDATA PALU, INDONESIA - Muhammad Ryman Napirah; Bertin Ayu Wandira; Ana Aulia (Public Health of Indonesia)
Background: Incidence of Multi Drug Resistant Tuberculosis remains high in Indonesia. Thus, understanding the factors related to the success of the Government Program on the treatment of Multidrug-resistant is necessity.